(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2025)
This paper examines the intersection of gender role, silence, and the quest for belonging in the identity formation of homosexual individuals within Indian families. Drawing on qualitative data from in-depth case studies, the research explores how gay men and lesbian women construct and express their sexual identity amidst cultural stigma, gendered expectations, and emotional isolation. The study uses Goffman’s theory of stigma, Cass and D’Augelli’s identity development models, and Maslow’s hierarchy of needs to analyze how individuals manage identity disclosure, perform gender roles strategically, and navigate familial rejection or silence. The findings suggest that family often becomes a contradictory space: emotionally central yet socially suppressive. Through the lived narratives of homosexual individuals, the paper highlights how silence becomes a survival strategy, and how gender role performance is manipulated to maintain social harmony. The research calls for a deeper sociological engagement with sexuality and family, urging inclusive policies and awareness that reflect the realities of queer lives in India.